Maintaining and restoring diversity - Majer, Jonathan (1992)
This chapter discusses the vulnerability of mediterranean ecosystems within Australia to disturbance and the ease with which they may be restored once they have been altered. In the absence of comparative studies on disturbance, the ecosystems in both hot (type Csa) and relatively cooler (type Csb) mediterraneanareas are looked at in terms of the phenophases of their various components. The possible influence of episodic disturbances in spring and autumn on these ecosystems is then postulated.Comparative data are available on the resilience of ecosystems in mediterranean Australia. Some studies suggest that mediterranean regions are more resilient than most non-mediterranean regions, although there is no evidence for difference in resilience between the different mediterranean regions of the world. By contrast, data on the return of ants in rehabilitated minesites in Australia suggest that. for this taxon at least. mediterranean regions exhibit lower resilience than the non-mediterranean regions which were investigated.